How concurrent thermomagnetic transitions can affect magnetocaloric effect: The Ni49+xMn36-xIn15 Heusler alloy case. (March 2019) - Law, Jia Yan; Díaz-García, Álvaro; Moreno-Ramírez, Luis M.; Franco, Victorino; Conde, Alejandro; Giri, Anit K.
Abstract: It is usually claimed that structural and magnetic transitions should coincide to improve the total entropy change. Here we show that overlapping structural and magnetic transitions can compete with each other, which gives rise to some signature of the competition misinterpreted as an experimental artifact of the measurements as observed in Ni49+x Mn36-x In15 (nominally x = 0, 0.5, 1.0, 1.5 and 2.0) investigated in this work. Their various magnetic phase transitions show a low temperature conventional magnetocaloric effect (MCE), an inverse MCE followed by another high temperature conventional MCE. For concurrent phase transitions with their respective transition temperatures close to one another, an observed spike embedded in the high temperature conventional MCE region is found arising from the martensitic transformation. We show that a crossover of the magnetic field dependence of the transition temperatures is obtained for concurrent phase transitions occurring in a narrow temperature range. As an evidence of the complexity of overlapping phase transitions, a recently proposed quantitative method for determining the order of phase transition is applied to this compositional series, showing its applicability even to cases when first- and second-order phase transitions occur in a narrow temperature range. Graphical abstract: Image 1